Synchronization of Coupled Map Lattice Using Delayed Variable Feedback - Arora, Siddharth; Santhanam, M.S. (Journal of Applied Nonlinear Dynamics, 2026)
We apply the method of variable feedback to obtain complete synchronization in a coupled map lattice. The conditions under which such a synchronization is possible are obtained analytically. We show that synchronization is robust against noise and parameter mismatches. This method leads to synchronized state quite rapidly and we discuss its applications for near-real-time multi-channel communications.